Relationship between obsessive compulsive disorder and cortisol: Systematic review and meta-analysis - Lima, João (2019)
Altered stress response and consequent elevated levels of circulating glucocorticoids have been found in neuropsychiatric disorders such as depression or anxiety disorders and proposed to also play a role in the pathophysiology of obsessive-compulsive disorder (OCD). Despite the observation that stressful events may precede the disease onset or even exacerbate its symptoms, studies in this field do not always report consistent results regarding the cortisol profile of OCD patients. As such, a systematic review and meta-analysis was developed to clarify this issue. This systematic review and meta-analysis was elaborated according to the PRISMA method. The analytical procedures were implemented using Metafor package in R software. Nineteen studies were included in the systematic review and 18 were included in the meta-analysis. The meta-analytic results demonstrated that OCD patients had significantly higher cortisol levels compared to controls (d = 0.76, SE = 0.146, p < 0.001). For studies using the average of multiple assessments, the standardized coefficient was significantly higher when compared to studies focusing on single measurements. Both the systematic review and meta-analysis suggest that cortisol levels are significantly higher in OCD patients than healthy individuals.